Dabigatran Added to Dual Antiplatelet Therapy to Treat a Left Ventricular Thrombus in an 87 Year Old Patient With Myocardial Infarction and Very High Bleeding Risk - Noflatscher, Maria; Moes, Nicolas; Gassner, Eva-Maria; Marschang, Peter (Frontiers in Pharmacology, 2018)
Background: A left ventricular (LV) thrombus is detected in approximately 5-10% of patients after myocardial infarction (MI). If left untreated, these LV thrombi carry a significant risk of complications including embolic stroke. According to current guidelines, anticoagulation with vitamin K antagonists (VKA) is recommended to treat a LV thrombus. Case presentation: An 87 year old patient was referred to our department with non ST-elevation MI. Five months before, he had been diagnosed with a subacute ST elevation MI, which had been treated conservatively. Recently, a rectal neoplasia had been diagnosed, but not operated yet. The patient underwent coronary angiography with implantation of two drug eluting stents (Cre8) requiring dual antiplatelet therapy. During ventriculography an apical LV thrombus of 16 mm diameter was detected. Due to the high bleeding risk in this patient, VKA therapy with potentially fluctuating international normalized ratio (INR) values was considered unsuitable. Therefore, dabigatran at a dose of 110 mg bid was chosen as anticoagulation therapy. After 4 weeks, cardiac computed tomography was performed, which failed to detect the LV thrombus described previously. Notably, triple therapy with dabigatran, clopidogrel and aspirin was well tolerated without evidence for bleeding. The surgical resection of the rectal neoplasm was performed 2 months later without bleeding complications. Discussion: Anticoagulation is effective in patients with MI and a LV thrombus in reducing the risk of embolization and in dissolving the thrombus. Our case is complex due to the required triple therapy, very old age and significant bleeding risk of our patient due to the rectal neoplasia . Although only few reports are available for the use of non VKA oral anticoagulants (NOAC) in this indication, we chose dabigatran at a dose of 110 mg bid added to dual antiplatelet therapy for our patient. Besides the advantage of a predictable pharmacokinetic profile of NOAC in contrast to VKA, the effect of dabigatran can rapidly be reversed by idaruzicumab in the case of severe bleeding. Conclusion remarks: Physicians should carefully weigh the risk of thromboembolic events versus the risk of bleeding when combining antiplatelet with anticoagulation therapy.